Poverty, Unemployment, Human Development, and Regional Economic Growth in South Sulawesi: Panel Evidence from an Islamic Economics Perspective - Muh Arafah; Anggun Suryani Hasmal; Azizi Abu Bakar; Nur Aliyah Rahma Saleh; Karina Kamista (Jurnal Ilmu Ekonomi dan Bisnis Islam, 2026)
Regional economic growth does not always lead to poverty reduction, labor absorption, or equitable welfare improvement. This study examines the relationship between poverty, the open unemployment rate, the Human Development Index (HDI), and regional economic growth across twenty-four regencies/municipalities in South Sulawesi during 2021–2025. Using balanced panel data, the study applies panel regression analysis, with the Common Effect Model selected through model specification tests. Because diagnostic tests indicate heteroskedasticity and first-order autocorrelation, the final estimation employs White period standard errors with cross-section clustering. The results show that poverty has a negative but statistically insignificant relationship with regional economic growth, while the open unemployment rate and HDI are also statistically insignificant. These findings suggest that short-term regional growth in South Sulawesi is not sufficiently explained by poverty, unemployment, and human development indicators alone, but may beinfluenced by broader structural factors, including sectoral composition, investment, public expenditure, infrastructure, and local recovery capacity. From an Islamic economics perspective, this study highlights the need to orient regional development beyond output expansion toward distributive justice, poverty reduction, productive employment, and welfare-based growth.